Issue of the Impact of Traffic Signs on Observance of Safe Distance Between Vehicles in the Czech Republic - Zemanek, Lukas (European Scientific Journal, ESJ, 2017)
This technical article deals with the issue of influence of road sign on observance of the safe longitudinal distance between vehicles on 1st class road in Czech Republic. It contains an analysis of vehicle accidents on the roads in the Czech Republic, focusing on the accidents caused by nonobservance of the safe distance. It also deals with the legislative requirements for the observance of the safe distance and at the conclusion, there is accomplished an analysis of influence of road sign on observance of the safe longitudinal distance between vehicles (classified by vehicle type) on the 1st class road in Czech Republic where is vertical and horizontal road sign to observe the safe distance between vehicles.